P35 Genomic profiling of intestinal-type sinonasal adenocarcinoma reveals a subgroup of patients with favourable clinical outcome. Issue 5 (May 2015) - López-Hernández, A.; Vivanco, B.; García-Inclán, C.; Costales, M.; López, F.; Llorente, J.L.; Hermsen, M.
Abstract : Introduction: Intestinal-type sinonasal adenocarcinomas (ITAC) are rare tumors, related to occupational exposure to wood and leather dust. Patients with ITAC carry a poor prognosis and recurrent disease is the main cause of mortality. The purpose of this study was to analyse genome-wide copy number alterations (CNAs) in a large series of cases, aiming to identify genetic events involved in ITAC development and progression. Material and methods: DNA was isolated from 61 frozen ITAC tissue samples including all histological subtypes and analysed by high-resolution microarray CGH. Results were correlated to previously obtained genetic and immunohistochemical data and to clinico-pathological characteristics and follow-up data. Results: All but three cases showed CNAs. Most frequent gains were found at chromosomal loci 5p, 7p, 8q, 12p and 20, whereas recurrent deletions were observed at 4q, 5q, 8p, 10q, 17p and 18q. High level amplifications included 7p12, 8q24, 11q13 and 19q11. Cluster analysis revealed a subgroup of cases characterized by carrying few CNAs (mean 8 versus 45). In addition, these cases showed absence of TP53 mutation and more frequent overexpression of COX2 and NFkB compared to the other cases. Overall survival was significantly better in this subgroup ( p  = 0.012). Conclusions: Genomic profiling revealed a subset of patients with ITAC with favourable clinical outcome, independent from established prognostic clinico-pathological parameters such as tumor stage and histological subtype. It may be speculated that this subset of tumors arises through a process of tumorigenesis that does not involved gross chromosomal instability as in the majority of epithelial tumors.